Sirtuin 6 inhibits group 3 innate lymphoid cell function and gut immunity by suppressing IL-22 production - Su, Xiaohui; Zhao, Linfeng; Zhang, Huasheng; Wang, Dongdi; Sun, Jiping; Shen, Lei (Frontiers in Immunology, 2024)
Introduction Group 3 innate lymphoid cells (ILC3s) are enriched in the intestinal mucosa and play important roles in host defense against infection and inflammatory diseases. Sirtuin 6 (SIRT6) is a nicotinamide adenine dinucleotide (NAD+)- dependent deacetylase and has been shown to control intestinal epithelial cell differentiation and survival. However, the role of SIRT6 in ILC3s remains unknown. Methods To investigate the role of SIRT6 in gut ILC3s, we generated SIRT6 conditional knockout mice by crossing Rorccre and Sirt6flox/flox mice. Cell number and cytokine production was examined using flow cytometry. Citrobacter rodentium infection and dextran sodium sulfate-induced colitis models were used to determine the role of SIRT6 in gut defense. RT-qPCR, flow cytometry and immunohistochemistry were used to assess the intestinal inflammatory responses. Results Here we show that SIRT6 inhibits IL-22 expression in intestinal ILC3s in a cell-intrinsic manner. Deletion of SIRT6 in ILC3s does not affect the cell numbers of total ILC3s and subsets, but results in increased IL-22 production. Furthermore, ablation of SIRT6 in ILC3s protects mice against Citrobacter rodentium infection and dextran sodium sulfate-induced colitis. Our results suggest that SIRT6 may play a role in ILC3 function by regulating gut immune responses against bacterial infection and inflammation. Discussion Our finding provided insight into the relation of epigenetic regulators with IL-22 production and supplied a new perspective for a potential strategy against inflammatory bowel disease.